ANALISIS PENGARUH KINERJA KEUANGAN, UKURAN PERUSAHAAN DAN STRUKTUR KEPEMILIKAN TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PADA PERUSAHAAN PERTAMBANGAN - Hidayat, Rahmad; Abidin, Khoirul (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2021)
The research aims to analyze the influence of financial performance, company size and managerial ownership structure on the timeliness of financial statement submission. The population of this study of mining companies listed on the Indonesia Stock Exchange in 2015-2019. This type of research is done with quantitative methods. The data collection method used in the study used a puposive sampling method with a sample of 10 companies over a 5-year observation period in a row, resulting in 50 samples. The analysis technique used for this test is logistic regression with the help of SPSS 25 software. Profitability, the size of the company affects the accuracy of the delivery of the company's financial statements while leverage, liquidity, ownership structure have no effect